Sexual functioning of middle-aged women: a literature review - Stusiński, Jarosław; Lew-Starowicz, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2012)
This article is a review of medical literature on the sexual functioning of middle-aged women. In studies on this issue, apart from the aspiration to improve the pharmacotherapy of sexual dysfunction, an equally strong emphasis is put on psychosocial and relational aspects of sexuality in this group. All these issues seem to be important for effective treatment of sexual problems in women of all ages.